Effigy Mounds, Social Identity, and Ceramic Technology: Decorative Style, Clay Composition, and Petrography of Wisconsin Late Woodland Vessels - (:unkn) unknown (My University, 2012)
This ceramic analysis is focused on a combination of technical and decorative analyses involving energy dispersive X-ray fluorescence (EDXRF) and petrographic data unused by or unavailable to previous researchers. The ceramics used in this study are non-collared forms of Late Woodland (AD 700 - 1200) types found across southern Wisconsin. Ceramic attributes from these data sets are analyzed using multi-variate statistical methods and the resulting clusters are plotted geographically. Results indicate regionalization of particular attributes with a major east-west trend noted in some cases. However, geographical plotting shows broad overlap among river valleys and locales. Importantly, EDXRF data demonstrates that ceramics or clays were transported across the landscape. The results are used to assess three models commonly used to explain Late Woodland group spatial distribution and interaction: Monolithic, Low-level Territorial, and High-level Territorial. However, while it is argued the Low-level Territorial model best respresents the data, the ceramic attributes indicate that multiple types of social organizations were practiced over space and time during the Late Woodland and that multiple territorial models are necessary to fully understand the social interactions occurring during this period. Finally, it is hypothesized that these results are best approached from a performance perspective where the social organization provides a contextual basis for investigating the daily performance of pottery making. Pottery manufacture is used to assess the constant making and re-making of social relationships at multiple levels of interaction in an egalitarian setting. It is hypothesized that different suites of attributes reflect different levels of group membership and that potters are consciously selecting attributes to negotiate these nested relationships through the practice of pottery construction.
Keywords: Ceramics; Decoration; Energy Dispersive X-Ray Fluorescence; Late Woodland; Petrography